2010
DOI: 10.1103/physrevb.81.064113
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure stability and compressibility ofAPO4(A=La, Nd, Eu, Gd, Er, and Y) orthophosphates: An x-ray diffraction study using synchrotron r

Abstract: Room temperature angle-dispersive x-ray diffraction measurements on zircon-type YPO 4 and ErPO 4 , and monazite-type GdPO 4 , EuPO 4 , NdPO 4 , and LaPO 4 were performed in a diamond-anvil cell up to 30 GPa using neon as pressure-transmitting † Corresponding author; email: daniel.errandonea@uv.es 2 medium. In the zircon-structured oxides we found evidence of a reversible pressureinduced structural phase transformation from zircon to a monazite-type structure. The onset of the transition is near 17 -20 GPa. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
110
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(138 citation statements)
references
References 44 publications
24
110
4
Order By: Relevance
“…In particular, a LeBail analysis allows indexing the pattern measured at 14.7 GPa with a CaSeO 4 -type structure (a = 6.88 Å , b = 5.88 Å, and c = 6.76 Å space group: P2 1 2 1 2 1 , Z = 4) similar to the high-pressure structure recently found in BaSO 4 [31]. The orthorhombic structure is a distortion of barite and its appearance as post-monazite phase in CeVO 4 is consistent with the fact that bariterelated structures have been found as HP phases in different monazites [13]. Barite and post-barite structures have been reported for high-pressure phases of CaSO 4 [32], BaSO 4 [31].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In particular, a LeBail analysis allows indexing the pattern measured at 14.7 GPa with a CaSeO 4 -type structure (a = 6.88 Å , b = 5.88 Å, and c = 6.76 Å space group: P2 1 2 1 2 1 , Z = 4) similar to the high-pressure structure recently found in BaSO 4 [31]. The orthorhombic structure is a distortion of barite and its appearance as post-monazite phase in CeVO 4 is consistent with the fact that bariterelated structures have been found as HP phases in different monazites [13]. Barite and post-barite structures have been reported for high-pressure phases of CaSO 4 [32], BaSO 4 [31].…”
Section: Resultssupporting
confidence: 86%
“…In contrast under non-hydrostatic conditions the zircon-to-scheelite transition has been detected. Both, non-hydrostatic effects and the change of the trivalent cation have been shown to play a role also in the structural behavior of zircontype arsenates, chromates, and phosphates [12,13]. Both factors deserve to be further studied into detail.…”
Section: Introductionmentioning
confidence: 96%
“…5� 10 -3 GPa -1 and κ c =1.3 � 10 -3 GPa -1 . The fact that the a-axis of zircon EuVO 4 is more compressible that the c-axis, is a typical behavior of zircon-structured oxides [47], in particular vanadates [7,14]. The origin of this behavior is related with the packing of EuO 8 and VO 4 polyhedral units in the zircon structure.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the most compressible axis is the c-axis. Since the scheelite and zircon structure are made of similar polyhedral units [47], the anisotropic behavior of scheelite can be explained using a similar argument which is used to explain the anisotropic compressibility of the zircon structure [45].…”
Section: Resultsmentioning
confidence: 99%
“…1,4,7,8 During the last decade, intensive investigations have been carried out on the structural evolution of MTO 4 -type ternary oxides under high-pressure (HP). They showed that compression is an efficient tool to improve the understanding of the main physical properties of vanadates, 9 phosphates, 10 chromates, 11 tungstates, 12 molydbates, 13 arsenates, 14 and many other MTO 4 compounds. 15 However, to the best our knowledge, an investigation of BiSbO 4 under pressure is still lacking in literature.…”
Section: Introductionmentioning
confidence: 99%